Find the best solutions to your questions at Westonci.ca, the premier Q&A platform with a community of knowledgeable experts. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To determine the expression equivalent to [tex]\(64 y^{18}-1000 z^6\)[/tex], we must rewrite the given expression in the form of [tex]\(a^3 - b^3\)[/tex]. Let's break this down step-by-step:
1. Identify possible values for [tex]\(a\)[/tex] and [tex]\(b\)[/tex]:
Start by recognizing that the given expression is in the form [tex]\(64y^{18} - 1000z^6\)[/tex].
We want to express both terms as cubes:
[tex]\[ a^3 = 64y^{18} \quad \text{and} \quad b^3 = 1000z^6 \][/tex]
2. Express [tex]\(64y^{18}\)[/tex] as a cube:
Notice that:
[tex]\[ 64 = 4^3 \quad \text{and} \quad y^{18} = (y^6)^3 \][/tex]
Hence, we can combine them as:
[tex]\[ 64y^{18} = (4y^6)^3 \][/tex]
3. Express [tex]\(1000z^6\)[/tex] as a cube:
Notice that:
[tex]\[ 1000 = 10^3 \quad \text{and} \quad z^6 = (z^2)^3 \][/tex]
Hence, we can combine them as:
[tex]\[ 1000z^6 = (10z^2)^3 \][/tex]
4. Combining both expressions:
Now we have:
[tex]\[ 64y^{18} = (4y^6)^3 \quad \text{and} \quad 1000z^6 = (10z^2)^3 \][/tex]
Therefore:
[tex]\[ 64y^{18} - 1000z^6 = (4y^6)^3 - (10z^2)^3 \][/tex]
Thus, the expression equivalent to [tex]\(64 y^{18} - 1000 z^6\)[/tex] is:
[tex]\[ \left(4 y^6\right)^3 - \left(10 z^2\right)^3 \][/tex]
Hence, the correct choice is:
[tex]\[ \boxed{\left(4 y^6\right)^3 - \left(10 z^2\right)^3} \][/tex]
1. Identify possible values for [tex]\(a\)[/tex] and [tex]\(b\)[/tex]:
Start by recognizing that the given expression is in the form [tex]\(64y^{18} - 1000z^6\)[/tex].
We want to express both terms as cubes:
[tex]\[ a^3 = 64y^{18} \quad \text{and} \quad b^3 = 1000z^6 \][/tex]
2. Express [tex]\(64y^{18}\)[/tex] as a cube:
Notice that:
[tex]\[ 64 = 4^3 \quad \text{and} \quad y^{18} = (y^6)^3 \][/tex]
Hence, we can combine them as:
[tex]\[ 64y^{18} = (4y^6)^3 \][/tex]
3. Express [tex]\(1000z^6\)[/tex] as a cube:
Notice that:
[tex]\[ 1000 = 10^3 \quad \text{and} \quad z^6 = (z^2)^3 \][/tex]
Hence, we can combine them as:
[tex]\[ 1000z^6 = (10z^2)^3 \][/tex]
4. Combining both expressions:
Now we have:
[tex]\[ 64y^{18} = (4y^6)^3 \quad \text{and} \quad 1000z^6 = (10z^2)^3 \][/tex]
Therefore:
[tex]\[ 64y^{18} - 1000z^6 = (4y^6)^3 - (10z^2)^3 \][/tex]
Thus, the expression equivalent to [tex]\(64 y^{18} - 1000 z^6\)[/tex] is:
[tex]\[ \left(4 y^6\right)^3 - \left(10 z^2\right)^3 \][/tex]
Hence, the correct choice is:
[tex]\[ \boxed{\left(4 y^6\right)^3 - \left(10 z^2\right)^3} \][/tex]
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're here to help at Westonci.ca. Keep visiting for the best answers to your questions.